Geological storage of COb2 (B:s modeling approaches for large-scale simulation - Celia, Michael Anthony; Nordbotten, Jan Martin, 1982- (Hoboken, NJ : Wiley, 2012)
'Despite the large research effort in both public and commercial companies, no textbook has yet been written on Carbon Capture and Storage (CCS). This book provides an overview, examining the dominant processes as well as the mathematical and numerical methods necessary to analyze the relevant systems. It provides an introduction to single-phase and multi-phase flow in porous media, including the most common mathematical analyses, and an overview of numerical methods for the equations. A considerable part of the book discusses appropriate modeling scales, including how to formulate consistent governing equations at these scales'--
'This book aims to provide an overview to the topic of Carbon Capture and Storage (CSS), while at the same time focusing on the dominant processes and the mathematical and numerical methods that need to be employed in order to analyze the relevant systems. The book clearly states the carbon problem and the role of CCS and carbon storage. Thereafter, it provides an introduction to single phase and multi-phase flow in porous media, including some of the most common mathematical analysis and an overview of numerical methods for the equations'--
Machine generated contents note: Prologue.Chapter 1. The Carbon Problem.Chapter 2. Single-Phase Flow in Porous Media.Chapter 3. Two-Phase Flow in Porous Media.Chapter 4. Large-Scale Models.Chapter 5. Solution Approaches.Chapter 6. Models for CO2 Storage and Leakage.Epilogue.Appendix.
Includes index.
Keywords: Geological carbon sequestration -- Mathematical models; TECHNOLOGY & ENGINEERING / Chemical & Biochemical